Contemporary Aspects of Legal Doctrine and Interpretation - Challenges and Perspectives - Riza, Arif; Faiku, Muharem; Kryeziu, Sidorela; Qatani, Valeri (Technium Social Sciences Journal, 2024)
In the countries where we have the construction of the legal system with the new laws, the ambiguity of the legal norms in the new laws in some cases is almost inevitable. But commenting on laws and judicial practice will be of great help to bring about the implementation of all legal norms as was the intention of the legislator, because the correct interpretation of legal provisions is a necessity of any legal order that creates a legal security for all citizens equally. Of course, the object of legal interpretation or clarification is not only written legal-civil norms, but also those that are part of customary law. The issue of interpretation of laws currently represents a fundamental concern for citizens and legal institutions, looking for a smart and innovative approach to address this issue effectively and sustainably. In this context, this paper aims to identify and analyze the advantages and challenges of legal doctrine and interpretation in the contemporary context.